The effect of indoor air quality (IAQ) towards occupants’ psychological performance in office buildings - Kamaruzzaman .S.N; Sabrani .N.A (Penerbit UKM, 2011)
Indoor air quality (IAQ) in a building is a very important element to ensure the health and comfort level of the building occupants. This is because work productivity may be interrupted due to the polluted environmental condition and bad indoor air quality. Both factors may lead to bad health and physical condition and consequently to bad work performance. The study presents the understanding and knowledge of how indoor air quality (IAQ) affects psychological performance and health impact to the occupants in government high rise office buildings in